The Ceremonies Of Longing - Kohler, Sandra, 1940- (Book collections on Project MUSE., 2003)
These beautifully lyric poems deftly explore imagination, relationships, and the unlived possibilities in our own lives. Kohler illuminates the magic that inhabits daily life and ordinary dreams.